Negotiating Islamic Symbols in Politics: Organisational Communication and Voter Attachment in Indonesia’s United Development Party - Bintang, Sadikin; Arifin, Zainal; Akbar, Ali (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Political ideology in electoral democracies increasingly functions as a communicative resource shaped by organisational practice rather than as a fixed doctrinal system. This study examines how the United Development Party (Partai Persatuan Pembangunan, PPP) in North Sumatra constructs and deploys Islamic symbols and narratives in its political communication, and how these practices relate to fluctuating electoral outcomes between 2014 and 2024. Using a qualitative interpretive design, the study draws on in-depth interviews with seven party actors involved in campaign coordination and message production, supported by field observations, internal party documents, and official electoral data. Empirically, ideological negotiation is identified through patterns of message centralisation, reliance on individual religious figures, and the presence or absence of sustained interaction with voters beyond campaign periods. The findings show that PPP’s communication generates strong symbolic recognition through Islamic imagery and moral language, yet fails to produce stable electoral attachment due to centralised message control, personalised narrative delivery, and episodic rather than continuous engagement with constituencies. Theoretically, the study reconceptualises Islamic ideology not as a symbolic style or rhetorical resource, but as an organisationally mediated communicative practice whose effectiveness depends on how meaning is institutionally produced, circulated, and maintained over time. By integrating Strategic Political Communication with Islamic communication principles, the study advances existing models by explaining why high ideological visibility does not necessarily translate into durable electoral support in local democratic contexts.